Mining Test Path Signatures For Analysis And Improvement Of Microchip Testing Programs - Lee, Jia Keat (2008)
A Test Program(TP) is constantly modified with the aim to reduce test cost. This research aims at revealing the effect of test changes on a microchip TP so that TP enhancement can be performed effectively.